Development of intelligent portable electronic nose - Abu Hassan, Abdullah; Abdul Hamid, Adom; Ali Yeon, Md Shakaff; Mohd Noor, Ahmad; A., Zakaria; Marni Azira, Markom; E.S., Tan; N.A., Fikri; Rakhmad Arief, Siregar; Mahamad Akmal, Saad (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.